Monteringsintruktioner i Augmented Reality En HoloLens-applikation för ihopvikning av kartongglasögon - HURTIG, ANTON; RAQI, BETIM (My University, 2017)
The investigations of this report aim to simplify manual sheets with the aid of Augmented Reality. Manual sheets in this case refer to the instruction papers that often come with commercial products that need some form of assemblying. An ARapplication has been developed to achieve this, which instructs the user how to fold some cardboard glasses into the commercial product. The application has been developed for the AR platform HoloLens, a leading product in the field. The application shows that AR is a suitable technology for simplifying manual sheets. With visual and interactive elements the user can see the whole assembly process and simultaneously assamble the physical product. The result of the investigations can be generalised to include other forms of instructions.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science